TINGKAT PROKRASTINASI AKADEMIK DALAM MENYELESAIKAN SKRIPSI PADA MAHASISWA AKTIVIS - Kholid Mawardi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2019)
Abstract: This thesis is a required scientific work as part of academic requirements at the University. All students must take thesis courses because the thesis is used as one of the prerequisites for students to obtain a bachelor's degree. Generally, students are given time to complete a thesis within one semester or approximately six months. In fact, many students need more than six months to work on their thesis. The research subjects were students who were members or activists of UKM. The cause of student procrastination is the lack of enthusiasm for working on the thesis, difficulty in getting the main book and supporting books, the fear of meeting the lecturers when they want to consult, being embarrassed to ask questions, and lazy to do it. Even among UKM activist students at IAIN Purwokerto (which is now called IAIN Purwokerto) prioritize activities in UKM rather than completing thesis. The results showed that UKM activist students in all majors had moderate procrastination rates based on the following academic procrastination categories: 13% were at very high levels, 20% were at high levels, 57% were at moderate levels, 10% were at low levels, and only 0% of student UKM activists in all majors have low procrastination rates. From these results it can be seen that on average students do procrastination. Keywords: Procrastination, Students, Thesis, Ukm Activists